An introduction to S Bases in S Linear Algebra - CARFI’, David (Journal of Mathematical Economics and Finance; Vol 5 No 2 (2019): JMEF, Volume V, Issue 2 Winter 2019, 2019)
In this lecture note we define the S bases for the spaces of tempered distributions. These new bases are the analogous of Hilbert bases of separable Hilbert spaces for the continuous case (they are indexed by m-dimensional Euclidean spaces) and enjoy properties similar to those shown by algebraic bases in the finite dimensional case. The S bases are one possible rigorous and extremely manageable mathematical model for the "physical" bases used in Quantum Mechanics.